Tanggung Jawab Belajar Siswa Dan Pengembangannya Melalui Layanan Bimbingan Konseling - Linggar Probo Ningrum; Amirah Diniaty (Fakultas Tarbiyah dan Keguruan, 2020)
This research aimed at knowing (1) student learning responsibility, (2) the role of Guidance and Counseling teachers in developing student learning responsibilitythrough guidance and counseling service at Vocational High School of Darel Hikmah Pekanbaru. Qualitative descriptive approach was used in this research. The population of this research was all of the students of Vocational High School of Darel Hikmah Pekanbaru that were 81 students. and the tenth-grade students that were 51 students were the samples. Questionnaire, interview, and documentation were the techniques of collecting the data. The data was analyzed by descriptive Qualitative percentage. After analyzing the data obtained in the field, it could be concluded that (1) learning responsibility was 74.20% and it was on high category, and (2)the roles of Guidance and Counseling teachers in developing student learning responsibility were (a) planning guidance and counseling programs, (b) conducting guidance and counseling service involving individual counseling service, group counseling service, information service, consultationservice, (c) evaluating the implemented services, (d) analyzing the results of the implemented services, (e) following up the services based on the needs of students.